Porcine Reproductive and Respiratory Syndrome Virus Antagonizes PCSK9’s Antiviral Effect via Nsp11 Endoribonuclease Activity - Zhang, Yujiao (Viruses, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogens in the swine industry worldwide. Our previous study had indicated that proprotein convertase subtilisin/kexin type 9 (PCSK9) was a responsive gene in porcine alveolar macrophages (PAMs) upon PRRSV infection. However, whether PCSK9 impacts the PRRSV replication and how the PRRSV modulates host PCSK9 remains elusive. Here, we demonstrated that PCSK9 protein suppressed the replication of both type-1 and type-2 PRRSV species. More specifically, the C-terminal domain of PCSK9 was responsible for the antiviral activity. Besides, we showed that PCSK9 inhibited PRRSV replication by targeting the virus receptor CD163 for degradation through the lysosome. In turn, PRRSV could down-regulate the expression of PCSK9 in both PAMs and MARC-145 cells. By screening the nonstructural proteins (nsps) of PRRSV, we showed that nsp11 could antagonize PCSK9’s antiviral activity. Furthermore, mutagenic analyses of PRRSV nsp11 revealed that the endoribonuclease activity of nsp11 was critical for antagonizing the antiviral effect of PCSK9. Collectively, our data provide further insights into the interaction between PRRSV and the cell host and offer a new potential target for the antiviral therapy of PRRSV.